Fast AV1 LocalWarped Motion Compensation Using Machine Learning - Kolodziejski, William; Braga, Leonardo; Rezende, Marcelo; Porto, Marcelo; Agostini, Luciano (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.14161, 2025)
The growing demand for high-efficiency video compression has driven the development of advanced codecs like AV1, which achieve superior compression rates but face challenges related to computational complexity. This paper addresses these challenges by proposing a machine learning-based optimization for the AV1 Local Warped Motion Compensation (LWMC) tool. This solution uses a Decision Tree model to skip unnecessary LWMC executions, reducing its processing time by 52% while maintaining a low impact on coding efficiency of only 0.21% in BD-BR. Compared to complete LWMC deactivation, our method demonstrates significantly better performance, particularly for content with complex motion patterns. To the best of the author’s knowledge, this is the first work in the literature to explore machine learning-based solutions applied to the AV1 LWMC tool.